Clinical profile of iron deficiency anemia in children from 6 months to 12 months of age - VERMA, DR ASHISH; VERMA, ASHISH (International Journal of Psychosocial Rehabilitation, 2020)
Background: Understanding the iron stores, would help us understand iron deficiency anemia better and help us combact with the associated comorbid conditions. Objectives: to assess severity of anemia ,to find out iron deficiency anemia is associated with which factors, to correlate other associated co morbid conditions. Methodology: a prospective observational study which will be conducted in avbrhospital on 75 patients. sample will be collected from IPD admissions in department of pediatrics. Results: after appropriate analysis with expect to assess iron deficiency anemia and its severity in children, factors causing iron deficiency anemia and correlate it with other co morbid condition. Conclusion: in this study we expect to observe profoundness of iron deficiency anemia in children with age group 6 months to 12 months of age. we also expect to see a positive association between anemia and weaning supplementary diet, we expect to find correlation of the anemia with other co morbid condition and also expect study to highlight clinical profile of children with IDA in this region.